Rudiments and Demurrals of Doctrine of Priority: Bangladesh Chapter (Dhaka University Law Journal, 2026)
In Bangladesh, the ownership, occupancy, and transfer of property are complicated because individuals in the country repeatedly purchase and sell the same property, despite the existence of laws. This may occur if the transfer is not adequately documented and possession is not delivered accordingly. Such a chaotic situation leads to suits paving the way for the superior courts making precedents, and the government departments framing guidelines, notifications, and statutory rules and orders (SROs), and the legislature making amendments to the existing laws or re-enactments. This article enlightens the doctrine of priority under the Transfer of Property Act, 1882, in conjunction with its essentials and exceptions. In order to have a better understanding, this particular concern has also been discussed through relevant case laws.Dhaka University Law Journal, 2025, 36(2), 77-95